A Rare Manifestation of Behçet's Disease; Arterial Involvement - Bozkurt, Erhan; Yalım, Zafer (International Journal of Innovative Research in Medical Science, 2017)
Behcet's Disease, also known as Behcet's syndrome, is a rare, chronic, autoimmune, auto inflammatory disorder of unknown origin. Its manifestations are thought to be caused by vasculitis resulting in damage to blood vessels throughout the body. The disease is named for the Turkish dermatologist, Dr. Hulusi Behcet, who in 1937 described a triad of oral ulcers, genital ulcers and ocular inflammation. In this case, we describe a case of acute myocardial infarction secondary to coronary artery involvement of Behçet's disease in a patient who was diagnosed with Behçet's disease 15 years ago from aphthous lesions in his mouth and genital area.